PENGARUH MODEL RME BERBANTUAN KUIS FORMATIF REFLEKTIF TERHADAP HASIL BELAJAR MATEMATIKA MATERI BILANGAN CACAH SISWA KELAS V SD TUNAS HARAPAN - Josephine Dwi Inarly Situmorang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of implementing the Realistic Mathematics Education (RME) model, supported by reflective formative quizzes, on the mathematics learning outcomes of fifth-grade students at Tunas Harapan Elementary School in the 2025/2026 academic year regarding the topic of whole numbers. This study employed an experimental method using a One-Group Pretest-Posttest Design. The study population consisted of 30 students, and the data analyzed were derived from students who completed both the pretest and posttest in full. The research instrument was a learning achievement test comprising 10 open-ended questions. The results showed that the mean post-test score of 82.55 was higher than the mean pre-test score of 75.33. Based on the results of the hypothesis test using the Wilcoxon Signed-Rank Test, the Asymp. Sig. (2-tailed) value was 0.046 < 0.05; therefore, H₀ was rejected and H₁ was accepted. Thus, it can be concluded that the implementation of the Realistic Mathematics Education (RME) learning model, supported by reflective formative quizzes, has a significant effect on the mathematics learning outcomes of fifth-grade students at Tunas Harapan Elementary School regarding the topic of whole numbers.